Spectrophotometric Determination of Cyanide and Hydrogen Cyanide Using p-Amino benzoic Acid as a New Reagent and Its Application in Steel Industries - Verma, A.K.; Gupta, V.K. (Asian Journal of Chemistry, 2010)
A new reagent system is proposed for the determination of cyanide and hydrogen cyanide. Cyanide is reacted with bromine and pyridine to form glutaconic aldehyde, which is then condensed with p-aminobenzoic acid to give a yellow orange dye extractable in n-butanol. Beer's law is obeyed over a concentration range of 0.02-0.2 ppm of cyanide at 410 nm. The molar absorptivity and Sandell's sensitivity were found to be 1.3 x 104 L mol-1cm-1, and 0.002 μg cm-1 respectively. The analytical parameters have been optimised and applied for the determination of cyanide in industrial effluent and air. The method has been favourably compared with ion selective electrode and other methods normally used in steel industries and found to be sensitive and specfic.